Causes, consequences, and cures for neuroinflammation mediated via the locus coeruleus: noradrenergic signaling system. (10th March 2016) - Feinstein, Douglas L.; Kalinin, Sergey; Braun, David
Abstract: Aside from its roles in as a classical neurotransmitter involved in regulation of behavior, noradrenaline (NA) has other functions in the CNS. This includes restricting the development of neuroinflammatory activation, providing neurotrophic support to neurons, and providing neuroprotection against oxidative stress. In recent years, it has become evident that disruption of physiological NA levels or signaling is a contributing factor to a variety of neurological diseases and conditions including Alzheimer's disease (AD) and Multiple Sclerosis. The basis for dysregulation in these diseases is, in many cases, due to damage occurring to noradrenergic neurons present in the locus coeruleus (LC), the major source of NA in the CNS. LC damage is present in AD, multiple sclerosis, and a large number of other diseases and conditions. Studies using animal models have shown that experimentally induced lesion of LC neurons exacerbates neuropathology while treatments to compensate for NA depletion, or to reduce LC neuronal damage, provide benefit. In this review, we will summarize the anti‐inflammatory and neuroprotective actions of NA, summarize examples of how LC damage worsens disease, and discuss several approaches taken to treat or prevent reductions in NA levels and LC neuronal damage. Further understanding of these events will be of value for the development of treatments for AD, multiple sclerosis, and other diseases and conditions having a neuroinflammatory component. The classical neurotransmitter noradrenaline (NA) has critical roles in modulating behaviors including those involved in sleep, anxiety, and depression. However, NA can also elicit anti‐inflammatory responses in glial cells, can increase neuronal viability by inducing neurotrophic factor expression, and can reduce neuronal damage due to oxidative stress by scavenging free radicals. NA is primarily produced by tyrosine hydroxylase (TH) expressing neurons in the locus coeruleus (LC), a relatively small brainstem nucleus near the IVth ventricle which sends projections throughout the brain and spinal cord. It has been known for close to 50 years that LC neurons are lost during normal aging, and that loss is exacerbated in neurological diseases including Parkinson's disease and Alzheimer's disease. LC neuronal damage and glial activation has now been documented in a variety of other neurological conditions and diseases, however, the causes of LC damage and cell loss remain largely unknown. A number of approaches have been developed to address the loss of NA and increased inflammation associated with LC damage, and several methods are being explored to directly minimize the extent of LC neuronal cell loss or function. In this review, we will summarize some of the consequences of LC loss, consider several factors that likely contribute to that loss, and discuss various ways that have been used to increase NA or to reduce LC damage. This article is part of the 60th Anniversary special issue . Abstract : The classical neurotransmitter noradrenaline (NA) has critical roles in modulating behaviors including those involved in sleep, anxiety, and depression. However, NA can also elicit anti‐inflammatory responses in glial cells, can increase neuronal viability by inducing neurotrophic factor expression, and can reduce neuronal damage due to oxidative stress by scavenging free radicals. NA is primarily produced by tyrosine hydroxylase (TH) expressing neurons in the locus coeruleus (LC), a relatively small brainstem nucleus near the IVth ventricle which sends projections throughout the brain and spinal cord. It has been known for close to 50 years that LC neurons are lost during normal aging, and that loss is exacerbated in neurological diseases including Parkinson's disease and Alzheimer's disease. LC neuronal damage and glial activation has now been documented in a variety of other neurological conditions and diseases, however, the causes of LC damage and cell loss remain largely unknown. A number of approaches have been developed to address the loss of NA and increased inflammation associated with LC damage, and several methods are being explored to directly minimize the extent of LC neuronal cell loss or function. In this review, we will summarize some of the consequences of LC loss, consider several factors that likely contribute to that loss, and discuss various ways that have been used to increase NA or to reduce LC damage. This article is part of the 60th Anniversary special issue .